2021
DOI: 10.48550/arxiv.2105.08424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher-Order Nodal Points in Two Dimensions

Abstract: A two-dimensional (2D) topological semimetal is characterized by the nodal points in its lowenergy band structure. While the linear nodal points have been extensively studied, especially in the context of graphene, the realm beyond linear nodal points remains largely unexplored. Here, we explore the possibility of higher-order nodal points, i.e., points with higher-order energy dispersions, in 2D systems. We perform an exhaustive search over all 80 layer groups both with and without spin-orbit coupling (SOC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…2(d) We find that the cubic Weyl point can exist in spinful type-II MLGs, consistent with the prediction in Ref. [52]. In addition, our result shows that it also exists in spinful type-I MLGs, but not in type-III and type-IV MLGs.…”
Section: Discussionsupporting
confidence: 91%
“…2(d) We find that the cubic Weyl point can exist in spinful type-II MLGs, consistent with the prediction in Ref. [52]. In addition, our result shows that it also exists in spinful type-I MLGs, but not in type-III and type-IV MLGs.…”
Section: Discussionsupporting
confidence: 91%
“…Such linear points locate at non-time-reversal invariant momentum (TRIM), and are enforced by C 3z and the spacetime inversion PT ð Þ symmetries. Most recently, there have been theoretical efforts 23,24 to conceive topological nodal points beyond the scope of linear nodal points. It has been discussed that a rotation symmetry (C 3z , na2) together with time-reversal symmetry T ð Þ can enforce a quadratic nodal point at TRIM in 2D spinless systems.…”
Section: Symmetry Protectionmentioning
confidence: 99%
“…Akin to the 3D case, Weyl points in spinless systems also have a higher dispersion. Most recently, Wu et al 23 and Yu et al 24 have demonstrated that the highest order of 2D Weyl points in a spinless system is quadratic. Inspired by the coexistence of different types of Weyl points in 3D, one may consider: Is it possible to stabilize a Weyl complex in a 2D phononic system?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is necessary to be noted that the highest order for the 2D nodal point is not limited to the linear dispersion; it could be up to the second-order in the absence of spin-orbital coupling (SOC). 14 The prominent example may be the bilayer graphene, [15][16][17][18][19][20][21] and it could host a nodal point with quadratic dispersion close to the Fermi level, giving rise to a new 2D quasiparticle excitation, dubbed as a double Weyl fermion, 22 underlying many novel physical consequences of bilayer graphene. Hence, it is of great interest to explore 2D materials that host novel topological excitations.…”
Section: Introductionmentioning
confidence: 99%